Hydroxychloroquine in Hospitalized Patients with COVID‐19: Real‐World Experience Assessing Mortality. Issue 11 (20th November 2020) - Annie, Frank H.; Sirbu, Cristian; Frazier, Keely R.; Broce, Mike; Lucas, B. Daniel
Abstract : Introduction : Hydroxychloroquine (HCQ) for coronavirus disease 2019 (COVID‐19) is presently being used off‐label or within a clinical trial. Objectives : We investigated a multinational database of patients with COVID‐19 with real‐world data containing outcomes and their relationship to HCQ use. The primary outcome was all‐cause mortality within 30 days of follow‐up. Methods : This was a retrospective cohort study of patients receiving HCQ within 48 hours of hospital admission. Medications, preexisting conditions, clinical measures on admission, and outcomes were recorded. Results : Among patients with a diagnosis of COVID‐19 in our propensity‐matched cohort, the mean ages ± SD were 62.3 ± 15.9 years (53.7% male) and 61.9 ± 16.0 years (53.0% male) in the HCQ and no‐HCQ groups, respectively. There was no difference in overall 30‐day mortality between the HCQ and no‐HCQ groups (HCQ 13.1%, n=367; no HCQ 13.6%, n=367; odds ratio 0.95, 95% confidence interval 0.62–1.46) after propensity matching. Although statistically insignificant, the HCQ‐azithromycin (AZ) group had an overall mortality rate of 14.6% (n=199) compared with propensity‐matched no‐HCQ–AZ cohort's rate of 12.1% (n=199, OR 1.24, 95% CI 0.70–2.22). Importantly, however, there was no trend in this cohort's overall mortality/arrhythmogenesis outcome (HCQ‐AZ 17.1%, no HCQ–no AZ 17.1%; OR 1.0, 95% CI 0.6–1.7). Conclusions : We report from a large retrospective multinational database analysis of COVID‐19 outcomes with HCQ and overall mortality in hospitalized patients. There was no statistically significant increase in mortality and mortality‐arrhythmia with HCQ or HCQ‐AZ.